2018
DOI: 10.1101/394254
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Therapeutic potential of TAF1 bromodomains for cancer treatment

Abstract: The discovery of the antiproliferative effects of BRD4 bromodomain inhibitors prompted us to investigate additional bromodomains that might be involved in supporting cellular proliferation.TAF1 is a general transcription factor with two bromodomains that is likely to play important roles in cell viability by supporting transcription. Our work shows that knock down of TAF1 caused antiproliferative effects in several cancer cell lines. Using CRISPR-Cas9 editing techniques we demonstrate that the bromodomains of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…I-CBP112 inhibition of p300 association with chromatin broadly across the genome resembles the behavior of several other bromodomain antagonists that have led to the dissociation of their cognate proteins from chromatin. [55][56][57] It is noteworthy that A-485rs acting on its own targeting the HAT "writer domain" also shows this behavior. One explanation for this is that A-485rs blocks histone acetylation and this in turn reduces the affinity of p300 for histones, via bromodomain interactions.…”
Section: Discussionmentioning
confidence: 94%
“…I-CBP112 inhibition of p300 association with chromatin broadly across the genome resembles the behavior of several other bromodomain antagonists that have led to the dissociation of their cognate proteins from chromatin. [55][56][57] It is noteworthy that A-485rs acting on its own targeting the HAT "writer domain" also shows this behavior. One explanation for this is that A-485rs blocks histone acetylation and this in turn reduces the affinity of p300 for histones, via bromodomain interactions.…”
Section: Discussionmentioning
confidence: 94%
“…Brennan et al 65 reported NSD1 mutation and DNA hypomethylation in patients with lung squamous cell carcinoma. Using the Cancer Genome Atlas data, Garci ́a-Carpizo et al 66 confirmed that NSD2 is highly expressed in lung cancer cells. The study showed that NSD2 is involved in the proliferation of a subset of lung cancer cells, including lung adenocarcinoma and squamous cell carcinoma via the Ras pathway.…”
Section: Functions Of Nsd1 Nsd2 and Nsd3 Inmentioning
confidence: 98%
“…Importantly, whereas BAY-299 impairs cell growth most likely by a TAF1-independent mechanism, [34] Tafbromin does not affect cell viability in different cell lines (Table S3). Inactivity of Tafbromin in NIH-3T3 cells may be due to low target expression or due to modulation of a differentiation…”
Section: Angewandte Chemiementioning
confidence: 99%